PERAN GURU DALAM PERSPEKTIF PROGRESIVISME PADA KURIKULUM MERDEKA - Rasyidah Wahdah (LPPM Universitas Muhammadiyah Bulukumba, 2024)
This research aims to describe the role of teachers in implementing the Independent Curriculum from the perspective of progressivism philosophy. Using the literature study method, this research analyzes various journals and related literature to identify teachers' responsibilities in bridging curriculum ideals with learning realities. The research results show that teachers are expected to be able to explore students' potential, design personalized learning, and develop students' character and creativity. In addition, teachers act as facilitators who support the development of 21st century skills through a collaborative classroom atmosphere. Developing teacher competency is an important aspect in implementing the Independent Curriculum, considering the importance of innovative skills and the use of technology in learning. This article concludes that the role of teachers is not only as transmitters of information, but also as agents of change who bring positive transformation in education.